Implementation of Teaching Factory to Improve Entrepreneurial Competence of Vocational High School Students - Maruanaya, Rita Fransina; Karuna, Kalvin; Tuhumena, Wilhemina Ascaria; Maruanaya, Greghar Juan Tjether (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2021)
According to data from the Central Statistics Agency (BPS), the unemployment rate in Indonesia in 2020 is still high at 9.77 million people or around 6.26% of the total productive age or labor force. When it was viewed from the level of education, it turned out that vocational high school graduates occupied the top position as a contributor to the unemployment rate in Indonesia, it was 13.55%. This high number of unemployed because the competence possessed by Indonesian human resources was still low or because there were not enough job opportunities to accommodate all graduates of the workforce. To overcome this, the government through the Ministry of Education and Culture, the Directorate of Vocational High School Education (SMK) was trying to find solutions to overcome these problems. This paper discussed a literature review about the teaching factory program in Vocational High Schools as one of the programs suggested by the government to be implemented in Vocational High Schools. Teaching factory was a learning activity where students directly carried out production activities in the form of goods and services in the school education environment, with the aim of training work competencies and having competencies for entrepreneurship. With the implementation of this program, it was expected that Vocational High School graduates were able to create jobs and at the same time opened up job opportunities for others and thus the unemployment rate in Indonesia could be suppressed